Overview Of The Perception Of Students Of The Faculty Of Medical HKBP Nommensen University Who Have Completed The Clinical Receptionary Year 2022 About Readiness For An Internship - Rudyn Reymond Panjaitan; Rebecca Rumesty Simamora; Bintang Febriyanti (Jurnal EduHealth, 2023)
The transition period from clinical clerkship to internship can affect student perceptions. During this transitional period students will experience a process of changing learning to apply their clinical knowledge. Some transitions can determine how much ability and self-evaluation is, but transitions can also change perceptions or good habits that have been applied to a person. Good preparation in terms of clinical skills before entering the internship period has been proven to be able to improve performance during the internship period such as communication and approach to patients, ability to motivate attitude, sense of initiative, and enthusiasm. To find out the description of the perceptions of students of the Faculty of Medicine, University of HKBP Nommensen who have completed clinical clerkships in undergoing internships. This research is a descriptive study with a cross-sectional approach using a sampling technique, namely purposive sampling. The description of the perceptions of students who have completed clinical clerkship regarding readiness to undergo internships with good perceptions is 25 people (57.55%), and with sufficient perceptions are 18 people (42.25%). The description of students' perceptions about readiness for the transition period and the socialization of the internship stage with good readiness were 21 people (48.8%) and with sufficient perceptions were 22 people (51.2%). The description of students' perceptions about readiness to face contact with patients with good readiness was 25 people (58.1%) and with sufficient perceptions 18 people (41.9%). The description of students' perceptions about readiness to deal with knowledge and skills with good perceptions was 30 people (69.8%) and with sufficient perceptions 13 people (30.2%). The majority of the descriptions of the perception of the readiness of students who have completed clinical clerkships regarding internships are good.